Implementasi Etika Bisnis Islam dalam Pemasaran Produk UMKM Pemindangan Ikan H. Udin di Desa Jatimulya, Kecamatan Rangkasbitung, Kabupaten Lebak - Kailla, Anastasya (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2026)
This study aims to analyze the implementation of Islamic business ethics in the marketing practices of H. Udin Fish Processing, a Micro, Small, and Medium Enterprise (UMKM), located in Kp. Ciseke, Jatimulya Village, Rangkasbitung District, Lebak Regency. This research employs a qualitative case study approach, with data collected through in-depth interviews and direct observations of the business owner, H. Udin. The results indicate that H. Udin consistently applies the principles of Islamic business ethics, such as honesty (ṣidq), justice (‘adl), trustworthiness (amanah), excellence (ihsan), and maintaining the halalness of products, throughout all stages of marketing, including product information delivery, pricing, promotion, distribution, and customer service. Despite facing challenges such as fluctuations in raw material prices, H. Udin maintains fairness and customer trust. The marketing strategy combines the 4P and 2P concepts in accordance with Sharia principles and utilizes information technology, such as WhatsApp and Facebook, to enhance transparency and communication with consumers. Overall, these marketing practices not only support business sustainability and blessing but also increase customer loyalty while ensuring the continuity of the business in a professional and modern manner.